2008
DOI: 10.1017/s1461145708009590
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the JAK-STAT pathway is necessary for desensitization of 5-HT2A receptor-stimulated phospholipase C signalling by olanzapine, clozapine and MDL 100907

Abstract: We previously demonstrated that olanzapine-induced desensitization of 5-HT2A receptor-stimulated phospholipase C (PLC) activity is associated with increases in RGS7 protein levels both in vivo and in cells in culture, and the increase in RGS7 is dependent on activation of the JAK-STAT pathway in cells in culture (Muma, et al., 2007;Singh, et al., 2007). In the current study, we found that desensitization of 5-HT2A receptor-stimulated PLC activity induced by olanzapine is dependent on activation of the JAK-STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Interestingly, in these systems, JAK-STAT activation was shown to mediate 5-HT 2A receptor desensitization (Singh et al, 2007(Singh et al, , 2009(Singh et al, , 2010. These previous observations coincide with our demonstration that directly activating the JAK/STAT pathway, through the IL-6 receptor system, attenuates DOI-induced 5-HT 2A receptor-mediated IP accumulation, substantiating the possibility of crosstalk between these receptor systems.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Interestingly, in these systems, JAK-STAT activation was shown to mediate 5-HT 2A receptor desensitization (Singh et al, 2007(Singh et al, , 2009(Singh et al, , 2010. These previous observations coincide with our demonstration that directly activating the JAK/STAT pathway, through the IL-6 receptor system, attenuates DOI-induced 5-HT 2A receptor-mediated IP accumulation, substantiating the possibility of crosstalk between these receptor systems.…”
Section: Discussionsupporting
confidence: 88%
“…, have also been shown to activate the JAK2-STAT3 pathway in both the neuronally derived A1A1 cell line (Singh et al, 2007(Singh et al, , 2009 and in the frontal cortex (Singh et al, 2010). Interestingly, in these systems, JAK-STAT activation was shown to mediate 5-HT 2A receptor desensitization (Singh et al, 2007(Singh et al, , 2009(Singh et al, , 2010.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, GWAS studies have also indicated that another SNP in RGS6 (rs2332700) is significantly associated with schizophrenia (25). The possible significance of RGS6's role in schizophrenia is further supported by preliminary studies which also suggest that RGS7 and RGS9 may be differentially expressed in patients with schizophrenia (86,87) and may modulate brain responses to psychostimulants and antipsychotics (49,(88)(89)(90)(91)(92)(93). Finally, not only is there substantial evidence detailing the critical role of various R7 family members in proper vision (94-97) but a splice acceptor variant of RGS6 (c.1369-1G>C) has also been positively associated with the familial inheritance of congenital cataracts (26).…”
Section: Alzheimer's Disease Schizophrenia and Eye-related Disordersmentioning
confidence: 88%